The effect of hyperglycaemia on haemostasis testing – a volunteer study. (31st December 2014) - Lippi, G.; Buonocore, R.; Musa, R.; Ippolito, L.; Picanza, A.; Favaloro, E. J.
Summary We investigated whether the contamination of samples with glucose subsequently tested for haemostasis affected the results, including prothrombin time, activated partial thromboplastin time and fibrinogen concentration. Venous blood was collected from 12 healthy subjects and divided into four aliquots, which were subjected to different degrees of contamination with standard glucose solution (0%, 5%, 10%, 20%). With increasing glucose contamination, prothrombin time increased from mean (SD) 11.0 (0.7) s to 11.2 (0.7) s, 11.5 (0.7) s and 12.2 (0.8) s, all p < 0.001. Activated partial thromboplastin time decreased from 32.3 (0.9) s to 30.9 (0.8) s, 30.8 (0.8) s, and 29.7 (0.7) s, all p < 0.001. Fibrinogen concentration decreased from 3.8 (0.7) g.l−1 to 3.7 (0.6) g.l−1, 3.6 (0.6) g.l−1, and 3.4 (0.6) g.l−1, all p < 0.001. Bias was clinically meaningful from 5% contamination for activated partial thromboplastin time, 10% contamination for prothrombin time and 20% contamination for fibrinogen concentration. We conclude that if glucose contamination of haemostasis samples is suspected or has occurred, the specimens should not be analysed.